2015
DOI: 10.1051/0004-6361/201424800
|View full text |Cite
|
Sign up to set email alerts
|

Neutron stars with hyperon cores: stellar radii and equation of state near nuclear density

Abstract: Context. The existence of 2 M pulsars puts very strong constraints on the equation of state (EOS) of neutron stars (NSs) with hyperon cores, which can be satisfied only by special models of hadronic matter. The radius-mass relation for these models is sufficiently specific that it could be subjected to an observational test with future X-ray observatories. Aims. We want to study the impact of the presence of hyperon cores on the radius-mass relation for NS. We aim to find out how, and for which particular stel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 46 publications
(61 reference statements)
12
91
2
Order By: Relevance
“…11). It should be stressed that both properties are valid for M < 0.9 M (stat) max [11]. The results reviewed above can be corroborated quantitatively by theoretical considerations.…”
Section: Keplerian (Mass-shedding) Limitsupporting
confidence: 63%
See 1 more Smart Citation
“…11). It should be stressed that both properties are valid for M < 0.9 M (stat) max [11]. The results reviewed above can be corroborated quantitatively by theoretical considerations.…”
Section: Keplerian (Mass-shedding) Limitsupporting
confidence: 63%
“…R ∞ can also be constrained by the modelling of the shape of the X-ray pulses observed from rotation-powered radio millisecond pulsars (RP-MSP) in particular if their mass is known from radio observations. Figure 1 shows the most recent constraints on the radius R 1.4 of a 1.4M NS obtained for various types of sources (see details in [11]). The constraints QXT-1 and RP-MSP being mutually exclusive, so far no consensus on R 1.4 can be reached.…”
Section: Radiusmentioning
confidence: 99%
“…However, in [67], it was shown that in order to prevent the EOS from violating causality, the radius should satisfy R 1.4 10.7 km, if it is imposed that the EOS also describes a 2 M star. In [45], taking experimental constraints and causality restrictions for large maximum masses, the 1.4 M star radii were constrained to be within the interval 12.1 ± 1.1 km (see [68]). …”
Section: Discussionmentioning
confidence: 99%
“…A summary and discussion of different observational radius determinations can be found in [22]. In addition, for a rotating star due to its deformation there is no unambiguous relation between the observed quantity and the radii determined theoretically.…”
mentioning
confidence: 99%